The Hybrid Flow Shop Scheduling With Special Time Constraints - Xiaobing Cheng; Mingping Xia; Xiuying Wang; Yongjun Xiao (Indonesian Journal of Electrical Engineering and Computer Science, 2014)
A constraint satisfaction optimization model is established for just-in-time HFS scheduling problem with limited waiting time. Considering the problem’s complicated characteristic of having binary variables, this paper decomposes it into a Multiple Capacitated Flow Shop Scheduling (MCFS) problem and a machine allocation problem. During the process of solving the MCFS problem, a local search is embedded into the procedure of constraint satisfaction optimization so as to improve the convergence of the algorithm. Data experiments show that both the model and algorithm are feasible and effective. DOI : http://dx.doi.org/10.11591/telkomnika.v12i5.5093